ANALISIS KESIAPAN PEMERINTAH DESA DALAM IMPLEMENTASI ALOKASI DANA DESA BIDANG PENDIDIKAN DI KECAMATAN GALANG - Zon Saroha Ritonga; Nurasyiyah Harahap (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2018)
The Government has established Law Number 6 Year 2014 concerning Villages and Village Minister Regulation Number 21 of 2015 concerning Priorities for the Use of Village Funds. The ideal allocation of village funds is to improve welfare and equitable distribution of rural development through improving public services in the village, advancing the village economy, overcoming the development gap between villages and strengthening village communities as subjects of development.This study aims to identify and describe the readiness of the village government, supporting factors and obstacles in the implementation of the Village Fund Allocation in the District of Galang.The method used in this study is a qualitative research approach. The collection of research data was obtained by triangulation techniques through observation, interviews and documents. The results of this study reveal the findings that the implementation of the Village Fund Allocation in the field of education is still minimum, the lack of understanding of the village apparatus regarding the use of the budget is the dominant factor. The use of village fund allocation is still focused on the development of village infrastructure such as road construction.